Impact of physiotherapeutic management for rehabilitation of patients with cardiovascular complications inherent to COVID-19 (Research, Society and Development, 2022)
The coronavirus 2019 (COVID-19) caused by SARS-COV-2 is correlated with the occurrence of severe acute respiratory syndrome, responsible for the global health crisis with social, economic and health consequences. Thus, the objective of the work was to gather knowledge about the most appropriate physiotherapeutic management for the rehabilitation of patients with cardiovascular complications inherent to COVID-19. For this, an integrative literature review was carried out, using the National Library of Medicine, National Institutes of Health (PubMed), Virtual Health Library and Science Direct as a database to search for articles. Of the 12 studies included in the survey, most cited heart failure (75%; 9/12) as the main cardiovascular complication associated with COVID-19 and in the same proportion (75%; 9/12) directly cited the importance of the physical therapist in rehabilitation of affected patients. Therefore, there is scientific evidence that emphasizes the relevance of physical therapy management in the rehabilitation of patients with cardiovascular complications associated with COVID-19.